A comparative content analysis of media reporting of sports betting in Australia: Lessons for public health media advocacy approaches - David, J.; Thomas, S.; Randle, M.; Bowe, S.; Daube, Mike (BioMed Central Ltd, 2017)
© 2017 The Author(s). Background: Harmful gambling is a significant public health issue. There has been widespread discussion in the Australian media about the extent and impact of sports betting on the Australian community, particularly relating to young men and children. Given the role th at the media plays in influencing policy change and political agendas, and the acknowledgement that media based advocacy is a fundamental component of successful advocacy campaigns, this research aimed to investigate how different stakeholder groups discuss sports betting within the Australian print media. The study uses this information to provide recommendations to guide public health media advocacy approaches. Methods: A quantitative content analysis of print media articles was conducted during two significant Parliamentary Inquiries about sports betting - (1) The Joint Select Committee Inquiry into the Advertising and Promotion of Gambling Services in Sport (2012/2013), and (2) 'The Review of Illegal Offshore Wagering (2015/2016). A total of 241 articles from 12 daily Australian newspapers were analysed. Statistical analysis was used to compare frequency of, and changes in, themes, voices and perspectives over time. Results: Discussions about the marketing and communication of sports betting was a main theme in media reporting (n = 165, 68.5%), while discussions about gambling reform decreased significantly across the two time periods (p < 0.0001). The presence of sports betting industry (p < 0.0001), sporting code (p < 0.0001) and public health expert (p = 0.001) voices all increased significantly across the two time periods. There were very few (n = 11, 4.6%) voices from those who had experienced gambling harm. Finally, while there were significantly fewer articles taking the perspective that regulation changes were needed to protect vulnerable sub-populations (p < 0.0001), articles that had a neutral perspective about the need for regulation change increased significantly across the two time periods (p < 0.0001). Discussion and conclusions: Mapping the media reporting of sports betting is important in developing effective public health advocacy approaches. This study indicates that discussions about the marketing strategies utilised by the sports betting industry was still a main theme in media articles. However, discussions relating to sports betting reforms, in particular to protect individuals who may be vulnerable to the harm associated with these products and their promotional strategies (for example children and young men) decreased during the time periods. Public health advocates may seek to address the decrease in media reports about reform by developing clear evidence-based messages about why regulatory reform is needed, as well as the potential consequences of not implementing reforms. Working with organisations to build capacity for people who have experienced gambling harm may help ensure that individuals with a lived experience of harm have an increased voice in the media.